2012
DOI: 10.1530/rep-12-0034
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the transepithelial calcium transport disruption and the formation of epididymal stones in roosters

Abstract: Epididymal lithiasis is a dysfunction of unknown origin characterized by the formation of calcium stones into the lumen of efferent ductules of roosters. Affected animals present an imbalance in the hormonal responsive systems that regulate the expression of proteins involved in the transepithelial calcium transport, as TRPV6, CaBP-D28K, NCX1, and PMCA. Because the efferent ductules are the major site of fluid and calcium reabsorption in excurrent ducts, it was hypothesized that impairment in local calcium hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…However, only TRPV6 is expressed in the male excurrent duct, as demonstrated in this study and others ( Weissgerber et al, 2011 ; Oliveira et al, 2012 ). TRPV5/TRPV6-mediated transcellular Ca 2+ absorption is a multistep process, which begins with passive Ca 2+ entry through apical Ca 2+ channels and is followed by diffusion of Ca 2+ through the cytosol, facilitated by binding to Ca 2+ -binding protein (calbindin-D 28k in the kidney and epididymis and calbindin-D 9K in the intestine) and eventually extrusion of Ca 2+ across the basolateral membranes by the energy-dependent Na + /Ca 2+ exchangers and Ca 2+ -ATPase operating against the Ca 2+ electrochemical gradient ( Hoenderop et al, 2005 ; Oliveira et al, 2012 ). From the point of view of energy input, it is suggested that the initial step of passive entry through TRPV5/TRPV6 channels in the apical membranes is the rate-limiting step.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, only TRPV6 is expressed in the male excurrent duct, as demonstrated in this study and others ( Weissgerber et al, 2011 ; Oliveira et al, 2012 ). TRPV5/TRPV6-mediated transcellular Ca 2+ absorption is a multistep process, which begins with passive Ca 2+ entry through apical Ca 2+ channels and is followed by diffusion of Ca 2+ through the cytosol, facilitated by binding to Ca 2+ -binding protein (calbindin-D 28k in the kidney and epididymis and calbindin-D 9K in the intestine) and eventually extrusion of Ca 2+ across the basolateral membranes by the energy-dependent Na + /Ca 2+ exchangers and Ca 2+ -ATPase operating against the Ca 2+ electrochemical gradient ( Hoenderop et al, 2005 ; Oliveira et al, 2012 ). From the point of view of energy input, it is suggested that the initial step of passive entry through TRPV5/TRPV6 channels in the apical membranes is the rate-limiting step.…”
Section: Discussionsupporting
confidence: 83%
“…TRPV5 is the predominant isoform found in kidney, whereas TRPV6 is found in the intestines, although these tissues coexpressed both isoforms in a region-dependent manner. However, only TRPV6 is expressed in the male excurrent duct, as demonstrated in this study and others (Weissgerber et al, 2011;Oliveira et al, 2012). TRPV5/ TRPV6-mediated transcellular Ca 2+ absorption is a multistep process, which begins with passive Ca 2+ entry through apical Ca 2+ channels and is followed by diffusion of Ca 2+ through the cytosol, facilitated by binding to Ca 2+ -binding protein (calbindin-D 28k in the kidney and epididymis and calbindin-D 9K in the intestine) and eventually extrusion of Ca 2+ across the basolateral membranes by the energy-dependent Na + /Ca 2+ exchangers and Ca 2+ -ATPase operating against the Ca 2+ electrochemical gradient (Hoenderop et al, 2005;Oliveira et al, 2012).…”
Section: Cell Phenotypessupporting
confidence: 78%
“…However, the restricted localization of the extracellular pH-and Ca 2+ -dependent TRPV6-TMEM16A electrical coupler in the proximal and distal ends of the epididymis as well as in the epididymosomes not associated with extensive Ca 2+ reabsorption could imply the presence of another calcium reabsorption mechanism or that TRPV6 and its coupler TMEM16A have a function other than Ca 2+ reabsorption. Consistent with our speculation, a study of roosters found that those with epididymal stones had raised epididymal expression of TRPV6, although the connection between the two observations is still unclear (Oliveira et al, 2012).…”
Section: Another Calcium Reabsorption Mechanism In Addition To Trpv6-...supporting
confidence: 86%
“…; Oliveira et al . ). In chicken, eggshell formation takes place in the uterus and demands plentiful ionic precursors for calcium carbonate (CaCO 3 ).…”
Section: Resultsmentioning
confidence: 97%